Reduction-Induced Suppression of Electron Flow (RISE) Is Relieved by Non-ATP-Consuming Electron Flow in Synechococcus elongatus PCC 7942 - Shimakawa, Ginga; Shaku, Keiichiro; Miyake, Chikahiro (Frontiers in Microbiology, 2018)
Photosynthetic organisms oxidize P700 to suppress the production of reactive oxygen species (ROS) in photosystem I (PSI) in response to the lower efficiency of photosynthesis under high light and low CO2 conditions. Previously, we found a positive relationship between reduction of plastoquinone (PQ) pool and oxidation of P700, which we named reduction-induced suppression of electron flow (RISE). In the RISE model, we proposed that the highly reduced state of the PQ pool suppresses Q-cycle turnover to oxidize P700 in PSI. Here, we tested whether RISE was relieved by the oxidation of the PQ pool, but not by the dissipation of the proton gradient (ΔpH) across the thylakoid membrane. Formation of ΔpH can also suppress electron flow to P700, because acidification on the luminal side of the thylakoid membrane lowers oxidation of reduced PQ in the cytochrome b6/f complex. We drove photosynthetic electron transport using H2O2-scavenging peroxidase reactions. Peroxidase reduces H2O2 with electron donors regenerated along the photosynthetic electron transport system, thereby promoting the formation of ΔpH. Addition of H2O2 to the cyanobacterium Synechococcus elongatus PCC 7942 under low CO2 conditions induced photochemical quenching of chlorophyll fluorescence, enhanced NADPH fluorescence and reduced P700. Thus, peroxidase reactions relieved the RISE mechanism, indicating that P700 oxidation can be induced only by the reduction of PQ to suppress the production of ROS in PSI. Overall, our data suggest that RISE regulates the redox state of P700 in PSI in cooperation with ΔpH regulation.